The Effect of Brand Image and Word of Mouth on the Decision to be a Customer of BTN Syariah Semarang - Fissilmi, Naily; Riyanto, Joko (Faculty of Economics and Business UNTAG Semarang, 2022)
BTN Syariah is one of the Islamic banking institutions that has become one of the recognized financial institutions in Indonesia. However, the market share of Islamic banking is still relatively small. This study aims to examine the effect of brand image and word of mouth (WOM) in influencing the decision to become a customer of Bank BTN Syariah. This research was conducted at BTN Syariah Semarang City used for data collection. The questionnaire instrument was used in this study. Validity and reliability testing was carried out first and multiple linear regression analysis was used for hypothesis testing. The results of the study found that each factor, namely brand image, had a positive influence on the decision to become a customer. Word of mouth also has a positive and significant influence on the decision to become a customer. This result implies that BTN Syariah must provide a lot of information so that it can improve brand image and word of mouth so that it can improve customer decisions.